A fejedelmi házaspár és a nevelés - BÁTORINÉ MISÁK, Marianna (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2019)
The royal couple and education. In this study, we discuss the attitudes of György I Rákóczi, prince of Transylvania and his wife, Zsuzsanna Lorántffy, towards education. First, after clarifying that the widely known painting depicting Zsuzsanna Lorántffy is not in fact her portrait, we examined the couple’s own education. We are convinced that this has determined the couple’s later behaviour, their relationship to education and the church. Biblical piety has been a very important element in their lives. They have grown up in this spirit since their childhood. They read the Bible every day, it was an integral part of their lives, as evidenced by their writings in their Bibles. Their piety, life, attitude, and church policy were based on the Bible. The education, whether in the lives of their own children, in educating their household, or in the establishment and support of educational institutions, has also manifested itself in an extraordinary way. We can say that György I Rákóczi and Zsuzsanna Lorántffy were neither typical parents, nor typical prince and princess. Besides trying to offer their own children the best education and teachers, they did not forget about educating their servants and their peasants on their estate. This is evidenced by their abundant donations, their orders, the gratitude of the teachers in the institutes, the lives and thanksgiving of the many preachers who receive many great opportunities and support.